STUDY TO EVALUATE CLINICAL PROFILE AND OUTCOME OF PATIENTS IN DIABETIC FOOT IN A TEACHING HOSPITAL - CH, NAGARAJU; VP, AKHILA; MADAR, PATHAN MASTAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to investigate the clinical characteristics and results of individuals who present with diabetic foot infections (DFI). Methods: This was a prospective study conducted in collaboration with the DFID Department of General Surgery at the Arundhati Institute of Medical Sciences and Hospital in Gandhimaisamma, Hyderabad, involving patients aged 20–80 years. Results: There were 55 patients in the current investigation, with a mean age of 61.78±11.75 years and a preference for males (n=45, 81.8%) over girls (n=10, 18.2%). The study’s largest number of patients (n=27, 49.1%) were observed in the 61–80 year age range. The average hemoglobin A1c (HBA1c) was 10.74±1.60 years, while the mean duration of diabetes mellitus was 10.87±2.681 years. Our patients’ microbiological profiles revealed that 32.7% of them were Gram positive and 67.3% were Gram negative. Gram-negative bacillus Escherichia coli was the most often found bacterium in our investigation (67.3%), followed by Pseudomonas (29.1%), Klebsiella (18.2%), and Staphylococcus aureus (5.5%). Conclusion: Since DFIs are the most prevalent consequence of diabetes mellitus that surgeons are notified about, managing them needs a multidisciplinary approach. It is crucial to do extensive, repeated examinations, as well as any required investigations to determine the infection severity at the time of presentation.